Human Resource Management of Baitul Maal wat Tamwil in the Digital: Challenges and Opportunities - Monalisa, Agnes; Sunarti, Gustiya (Institut Agama Islam Negeri Parepare, 2024)
This study examines the challenges and opportunities faced by Baitul Maal wat Tamwil (BMT) in managing human resources (HR) in the rapidly evolving digital era. The main focus is to analyze HR adaptation strategies that align with technological advancements while upholding the Sharia principles that form the foundation of BMT’s operations. Utilizing a qualitative method and a literature review approach, the study synthesizes findings from various relevant sources and previous research. The analysis reveals that digitalization within BMT requires not only adequate technological infrastructure but also an improvement in digital competencies among all levels of human resources, from operational staff to management. Furthermore, the digital transformation calls for a shift in work culture toward a more adaptive, collaborative, and technology-oriented approach. These findings imply that BMT must actively integrate information technology into its work systems, conduct regular training focused on digital competencies within a Sharia framework, and build a work ecosystem that encourages innovation while remaining grounded in Islamic values. Such strategic efforts are essential to ensure that BMT remains competitive, relevant, and capable of sustainably meeting community needs amid ongoing change.